Pengamatan Pengobatan Kanker Leher Rahim dengan Kombinasi Radiasi dan Khemoterapi serta Radiasi Saja - Djuita, Fielda; -, Dewi; Ranuhardi, Doddy; Tadjudin, Hilman; Dwipoyono, Bambang; -, Sumannadi; -, Nasdaldy (National Cancer Center - Dharmais Cancer Hospital, 2007)
Several clinical trial reported that chemo radiation has significant and equivalent improvement in pelvic failure and overall survival for uterine cervical cancer copared with radiation alone. The best result is certainly achieved by careful attention to management, including the overall treatment time because prolongation overall treatment time will reduce survival. For that reasons lue have reviewed 52 patients ; 14 patients without chemotherapy, 14 patients with chemotherapy docetaxel, 14 patiens with chemotherapy cisplatin and 10 patiens with paclitaxel. 33 patient stage HB and 19 patient stage 1UB. All patients received external radiation in prone position with 50 Gy dose and brachytherapy 3 X 70 Gy at point A. All patients clinically complete respons except 2 patients partial respons from group radiation alone and docetaxel but the overall treatment times from groups cisplatine and paclitaxel longer than others.Key words; Radiation, Uterine Cervical Cancer, Sensitizer Chemotherapy.